Penerapan Model Pembelajaran Student Facilitator And Explaining Untuk Meningkatkan Hasil Belajar PAI di Kelas III SDN Gelam 2 - Yuspita, Leni; Robiansyah, Firman; Darmawan, Darmawan (Edification Journal : Pendidikan Agama Islam, 2023)
A good learning process with the involvement of both parties between teachers and students. Therefore, in the research conducted by this researcher will describe a use of the Student Facilitator and Explaining learning model to be applied during the learning process in PAI subjects in improving student learning outcomes. The research approach used is a qualitative approach and runs using the Classroom Action Research (PTK) method. The study was conducted with 3 cycles in 3 meetings on the content of PAI subjects. In each cycle there is an action with student learning outcomes in each cycle. In cycle I obtained an average value of 66.86 with a percentage of completeness of 64.28% then in cycle II it increased to 72.43 with a percentage of completeness of 67.85% and increased again in cycle III to 79.15 with a percentage of completeness of 73.1%. Then the results of student activity observations stated that the learning process that tends to increase from cycle I obtained a percentage of 58% to cycle III to 75%. This can show that the student facilitator and explaining learning model can improve student PAI learning outcomes in grade III SDN Gelam 2.